The Representation of ‘The Other’ towards Little Bee’s Character in Chris Cleave’s The Other Hand Novel: A Postcolonial Analysis - Annisa, Awaliah Nur; Kuncara, Singgih Daru; Nasrullah, Nasrullah (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2019)
The aims of this research are to identify the representations of the Other in one of the main characters in Chris Cleave’s The Other Hand novel named Little Bee and to describe the way the author characterized those representations to the character. In this research, the researcher used qualitative research methodology and postcolonialism approach in analyzing the novel. Further, the theories that are used in this analysis are the theories of the representation of the Other in reference to four experts (Said, Bertens, Al-Saidi and Tyson) and Kenan’s theory of characterization. The result of this thesis shows that Little Bee as one of the most important character in the novel reflected the representations of the Other within herself. Those representations of the Other are different, foreign, inappropriate, inferior, irrational, passive, primitive, savage and unauthorized. In this case, the findings show that those representations are characterized in Little Bee’s character mostly in indirect presentation and it is found that only two data which are characterized in direct presentation.Tujuan dari penelitian ini adalah untuk mengidentifikasi representasi Liyan dalam salah satu karakter utama dalam novel Chris Cleave the Other Hand bernama Little Bee dan menggambarkan cara penulis mengkarakterisasikan representasi-representasi tersebut kedalam karakternya. Dalam penelitian ini, peneliti menggunakan metodologi penelitian kualitatif dan pendekatan poskolonial. Selanjutnya, teori yang digunakan adalah representasi Liyan dengan referensi empat ahli (Said, Bertens, Al-Saidi, dan Tyson) dan teori karakterisasi Kenan. Hasil penelitian menunjukkan bahwa Little Bee sebagai salah satu karakter utama dalam novel merefleksikan representasi Liyan dalam dirinya. Representasi tersebut adalah berbeda, asing, tidak pantas, rendah, tidak rasional, pasif, primitif, biadab dan tidak sah. Dalam hal ini, representasi-representasi tersebut dikarakterisasikan kedalam karakter Little Bee rata-rata dalam presentasi secara tidak langsung dan ditemukan bahwa hanya dua data yang mengkarakterisasi Little Bee dalam presentasi secara langsung.